DRONE AWARENESS WORKSHOP CGIAR Initiative on Digital Innovation in Collaboration with CLEARSKIES Pvt. Ltd. - CGIAR Initiative on Digital Innovation; CLEARSKIES (2023)
CG Initiative on Digital Innovation and ClearSkies. 2023. Drone Awareness Workshop, Bengaluru, India, June 27, 2023